ANALISIS KONDISI KEUANGAN DAERAH KABUPATEN/KOTA DI ACEH DAN DI SUMATERA UTARA - Suryani .; Hasan Basri; Faisal . (Jurnal Bisnis dan Ekonomi, 2016)
The indicators of a successful regional autonomy are an increase in public services and social welfare, more advanced democratic life, justice, equity and the existence of harmonious relations between Center and Regions as well as among Regions. In facts, only few areas that is able to manage various type of local revenue potential maximally, so as to significantly and gradually realize the independence of local finance. This study was conducted to examine and analyze the financial condition of local government in Aceh and North Sumatra for fiscal year 2011-2013 by using Mann-Whitney U Test. The results showed that (1) districts/cities in Aceh have a better level of local financial condition than districts/cities in North Sumatra based on total regional income/total population ratio, regional taxes and levies/GDRPratio, and previous year of unused funds (SiLPA)/regional expenditures ratio; and (2) districts/cities in North Sumatra have a better level of local financial condition than districts/cities in Aceh based on capital expenditure/total regional expenditures ratio. This study implied that local government in Aceh should focus more on the efforts to improve the genuine regional income (PAD) and prioritize the principle of efficiency as well as budget priorities. Keywords: ratio analysis, financial condition of local government.